ANALYSE DE LA POPLITIQUE HYDRIQUE EN ALGERIE DEPUIS L’INDEPENDENCE - CHAOUI, Mohamed Sofiane; BENTERKI, Azzedine; VAN CAUWENBERGH, Nora (Journal of Human Sciences, 2016)
Like the other countries in the region, given its position in an arid and semi-arid climate, Algeria has suffered and will suffer from any scarcity of the indispensable resource for life on earth, which is why the authorities opted through different planes (three-year and five-year) various programs of investment in the water sector that have reached 22.5 billion until 2008 with the estimate to reach 35.71 billion in 2025.But yet to assess the effectiveness of these colossal sums and measure the return on investment, a value that is expressed in the form of Well-Being of the population and the impact of the resource on the socio-economic development in terms of economic contribution. Unrealistic goals are set during the development of water saving and modernization program as a unilateral decision, while history shows us that it is utopian visions, however these approaches are implemented by the allocation of huge sums without much guarantee or at least evaluate the effectiveness of programs developed and their impact on the socio-economic sphere and/or societal. As these amounts will not be helpful as governance is not assured with an effective strategy to be more realistic and to achieve the targeted goals.